Online and Distance Education in the Modern Era - Siti Nuraeni Mitra; Entan Sutisna; Cecep Hilman (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2023)
Online and distance education have become important topics in the modern era, especially during the COVID-19 pandemic. Regulations on online education and PJJ vary across countries and regions, but in most cases, government agencies and educational institutions have issued guidelines and policies to ensure that online learning and PJJ are effective and safe. The mechanisms and types of learning in online education and PJJ also vary. .. The approach used is descriptive qualitative, namely research that does not use mathematical, statistical or computer models. The analytical method is library research, namely library-based research. The results of the discussion show that online and distance education in the modern era in learning is carried out using several methods that are quite effective. The suggestions put forward by researchers are that distance learning has several obstacles, one of which is not all parents can guide learning at home because of work matters, so it needs to be coordinated properly between teachers and parents, when learning or material is given to students so that students later ready to work with the guidance of his parents at home. Online learning has great potential to expand access to education and increase learning efficiency. However, keep in mind that online learning is not a one-size-fits-all solution. Keywords: Long Distance, Modern Era, Online Education